Use of systemic corticosteroids for atopic dermatitis: International Eczema Council consensus statement. (28th January 2018) - Drucker, A.M.; Eyerich, K.; de Bruin‐Weller, M.S.; Thyssen, J.P.; Spuls, P.I.; Irvine, A.D.; Girolomoni, G.; Dhar, S.; Flohr, C.; Murrell, D.F.; Paller, A.S.; Guttman‐Yassky, E.
Summary: Background: Guidelines discourage the use of systemic corticosteroids for atopic dermatitis (AD), but their use remains widespread. Objectives: To reach consensus among an international group of AD experts on the use of systemic corticosteroids for AD. Methods: A survey consisting of statements accompanied by visual analogue scales ranging from 'strongly disagree' to 'neutral' to 'strongly agree' was distributed to the International Eczema Council (IEC). Consensus was reached in agreement on a statement if < 30% of respondents marked to the left of 'neutral' towards 'strongly disagree'. Results: Sixty of 77 (78%) IEC members participated. Consensus was reached on 12 statements, including that systemic corticosteroids should generally be avoided but can be used rarely for severe AD under certain circumstances, including a lack of other treatment options, as a bridge to other systemic therapies or phototherapy, during acute flares in need of immediate relief, in anticipation of a major life event or in the most severe cases. If used, treatment should be limited to the short term. Most respondents agreed that systemic corticosteroids should never be used in children, but consensus was not reached on that statement. The conclusions of our expert group are limited by a dearth of high‐quality published evidence. If more stringent consensus criteria were applied (e.g. requiring < 20% of respondents marking towards 'strongly disagree'), consensus would have been reached on fewer statements. Conclusions: Based on expert opinion from the IEC, routine use of systemic corticosteroids for AD is generally discouraged and should be reserved for special circumstances. Abstract : What's already known about this topic? Despite recommendations against their use in practice guidelines, systemic corticosteroids are commonly used for atopic dermatitis (AD). What does this study add? The International Eczema Council reached consensus on circumstances in which systemic corticosteroids can be used for AD, including a lack of other treatment options, as a bridge to other systemic therapies or phototherapy, during acute flares in need of immediate relief, in anticipation of a major life event, or in the most severe cases. Clinicians should limit the use of systemic corticosteroids for severe AD to those circumstances. Plain language summary available online Respond to this article